2011
DOI: 10.1111/j.1467-9507.2011.00618.x
|View full text |Cite
|
Sign up to set email alerts
|

Relations over Time among Children's Shyness, Emotionality, and Internalizing Problems

Abstract: Data regarding children's shyness and emotionality were collected at three time points, two years apart (T1: N = 214, M = 6.12 years; T2: N = 185, M = 7.67 years; T3: N = 185, M = 9.70 years), and internalizing data were collected at T1 and T3. Relations among parent-rated shyness, emotionality (parent- and teacher-rated anger, sadness, and positive emotional intensity [EI]), and mother-rated internalizing were examined in panel models. In some cases, shyness predicted emotionality two years later (teacher-rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
1
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(46 citation statements)
references
References 52 publications
(78 reference statements)
2
40
1
2
Order By: Relevance
“…This result suggests that conflicted shyness may be a risk factor for externalizing problems in boys specifically during middle to late childhood, but not from early to middle childhood. However, this stands in contrast to other studies that have found non-significant or negative relationships between shyness and externalizing symptoms (e.g., Eggum et al, 2012; Coplan et al, 2004; Coplan & Weeks, 2010), one of which also found no gender differences in effects (Eggum et al, 2012). The relationship between social withdrawal and externalizing outcomes in boys versus girls should continue to be explored in future research.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…This result suggests that conflicted shyness may be a risk factor for externalizing problems in boys specifically during middle to late childhood, but not from early to middle childhood. However, this stands in contrast to other studies that have found non-significant or negative relationships between shyness and externalizing symptoms (e.g., Eggum et al, 2012; Coplan et al, 2004; Coplan & Weeks, 2010), one of which also found no gender differences in effects (Eggum et al, 2012). The relationship between social withdrawal and externalizing outcomes in boys versus girls should continue to be explored in future research.…”
Section: Discussioncontrasting
confidence: 99%
“…For instance, Eggum et al (2012) found that, adjusting for baseline levels of symptoms, conflicted shyness was related to increases in internalizing symptoms over 2 years, while Karevold et al (2012), although they did not use the CSPS, found that increases in shyness from age 2.5 years to 12.5 years was associated with increases in depression and anxiety symptoms over that interval.…”
Section: Childhood Social Withdrawal and Later Internalizing Outcomesmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, internalizing symptoms (with stronger effects for depression) have been characterized by an absence of self-reported positive affect (Clark & Watson, 1991; Lonigan, Phillips, & Hooe, 2003). To date, the research literature indicates that the associations of positive emotionality (usually undifferentiated in regard to intensity vs. frequency) to children’s internalizing or externalizing difficulties in nonclinical samples are typically nonsignificant (Eggum et al, 2012; Ghassabian et al, 2014; Kim et al, 2007) or negative (Dougherty, Klein, Durbin, Hayden, & Olino, 2010; Ghassabian et al, 2014; Kim et al, 2007; Stifter, Putnam, & Jahromi, 2008), but occasionally positive (when positive emotionality was characterized by exuberance; Putnam, 2012). Positive emotion also likely contributes to positive social interactions and competence (Jones, Eisenberg, Fabes, & MacKinnon, 2002; Lyubomirsky, King, & Diener, 2005).…”
Section: Emotion Expressivity Externalizing and Internalizing Problmentioning
confidence: 99%